Damage behaviour of concrete face slab for rockfill dam under the action of high frequency and large amplitude reservoir water circulation - Lifeng Wen; Haokang Lin; Yanlong Li; Shaobo Sun (European Journal of Environmental and Civil Engineering, 2026)

Aerobic exercise improve physical endurance and muscle function by ameliorating oxidative stress and modulating mitochondrial dynamics in aged skeletal muscle - Fengting Zheng; Jiawei Zhou; Yangfan Cao; LuYi Lin; Wenxin Wang; Liang Zhang; Wei Li; Ting Li; Lifeng Wang (Journal of Physiology and Biochemistry, 2026)

Rhamnogalacturonan I in commercial samples of polygalacturonic acid is a functional driver: A study of isolation, structural elucidation, role in immunostimulation and hydrogel mechanics - Xueting Zhang; Chuying Huo; Pengfei Shan; Niping Chen; Quanwei Zhang; Hauyee Fung; Wenting Zhao; Jing Li; Peili Zhu; Shanlong Tang; Ye Yuan; Lin Sun; et al. (Food Hydrocolloids, 2026)

A review on the formation mechanisms, influencing factors, and applications of the cold-induced gel of egg white protein - Yanqiu Ma; Lin Lin; Qing Liu; Xiaoxue Yang; Xin Gao; Yaotong Liu; Huajiang Zhang; Lifeng Wang (Food Hydrocolloids, 2026)

Performing comprehensive nutrient recovery through the integration of selective electrodialysis with reverse osmosis by using synthetic swine wastewater - Jingwei Xu; Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Yenan Li; Lifeng Lin (Desalination, 2026)

A novel model (SED-GNDE) integrating graph neural differential equations with selective electrodialysis process for nutrient prediction from synthetic wastewater - Yahui Huang; Zhi-Long Ye; Xiaofang Pan; Jianzhi Huang; Lifeng Lin (Water Research, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Impacts of sea surface temperature anomalies on the variability of wintertime explosive cyclone wind destructive potential over the North Pacific - Min Yang; Peilong Yu; Xiaopei Lin; Cheng Sun; Lifeng Zhang; Yunying Li (Atmospheric Research, 2026)

Cu-feed-ratio-regulated FeCoNiCr-based layered double hydroxide catalysts for efficient and durable oxygen evolution in anion exchange membrane water electrolyzers - Wei Liao; Kaiyang Xu; Haoliang Huang; Xixi Wang; Fei Lin; Zhipeng Yu; Chenyue Zhang; Yue Mi; Hang Cui; Liyuan Zeng; Weimian Zhang; Lijian Meng; et al. (Chemical Engineering Journal, 2026)

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Adaptive Multi-Scale Frequency-Domain Reconstruction for Multi-Source Gravity Data Fusion - Menghan Xi; Lin Wu; Zuoqin Shi; Qianqian Li; Shi Liu; Lifeng Bao (Journal of Marine Science and Engineering, 2026)
The gravity navigation reference map is a foundational element of gravity matching-aided navigation systems, as it directly determines positioning accuracy and overall navigation performance. To improve fused gravity anomalies and reduce reliance on manually selected parameters, this study proposes an adaptive multi-scale frequency-domain reconstruction (AMFR) algorithm. Specifically, the target ocean covered by multi-source satellite gravity data is divided into multiple scales, and distinct fusion parameters are assigned according to the characteristics of multi-source gravity data in different sea areas to enhance the accuracy of the fused gravity navigation reference map. Seven fusion schemes with different filtering diameters and weighting strategies are designed for comparative analysis. We evaluate the algorithm’s performance using measured gravity data with varying spatial distributions from the South China Sea and the Western Pacific Ocean, employing both RMS comparison and matching positioning experiments. Experimental results demonstrate that the RMS of the gravity navigation reference map constructed by the proposed AMFR algorithm is reduced by 30.4%, and the matching positioning accuracy is improved by 23.4%. The AMFR algorithm effectively enhances the precision of the gravity navigation reference map and improves the navigation performance of the gravity matching-aided navigation system.

CuI additive induced co-regulation of ion transport and interfacial chemistry in poly(ethylene oxide)-based solid-state electrolytes for improved battery performance - Kepan Yan; Xuexiao Chen; Haoliang Huang; Zicong Yu; Jingcheng Lu; Zhipeng Yu; Sitaramanjaneya Mouli Thalluri; Jinfeng Zeng; Wei Wang; Fei Lin; Yijuan Li; Weicai Zhang; et al. (Chemical Engineering Journal, 2026)

Precise structural characterization and therapeutic potential of a glucomannan polysaccharide from dried rhizome of plant Bletilla striata against ulcerative colitis - Huidan Hou; Lifeng Li; Tahidul Islam; Jingchun Shi; Mengyang Hou; Siliang Jiang; Xiaohan Zhao; Chengyuan Lin; Quanbin Han; Lin Zhu; Zhaoxiang Bian (Carbohydrate Polymers, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Moisture-Proof Herbal Extract Pellets Prepared via Asymmetric Liquid Layering Technology Combined with Mesoporous Silica and Magnesium Stearate - Shilin Ma; Yupeng Feng; Panao Yuan; Yunlong Xu; Ping Shao; Lifeng Lin; Zimin Wang; Ling Han; Xing Tang (AAPS PharmSciTech, 2026)

Leaf spot disease on Viburnum odoratissimum caused by Corynespora cassiicola and Colletotrichum species in China - Feng Lin; Xiaojie Peng; Kai Cai; Haonan Wang; Lifeng Zhou; Xudong Zhou (Crop Protection, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

From chemisorption to physisorption: A synergistic computational screening approach to exploit N-rich covalent organic frameworks for methyl iodide capture - Tianyu Guo; Xiaoyu Wu; Chenrui Li; Liangdan Zhao; Mingrui Zuo; Lin Liu; Lin-Bing Sun; Lifeng Ding (Chemical Engineering Journal, 2025)

Slippage-suppression robot-assisted retraction for thyroid surgery with 5DoF contact force sensing - Shouhui Deng; Haojun Li; Yuxuan Lin; Aiguo Song; Lifeng Zhu (Medical & Biological Engineering & Computing, 2025)

Synergistic Fe S sites on paper sludge-derived biochar activating peroxymonosulfate via a singlet oxygen-enhanced pathway for efficient 2,4,6-trichlorophenol degradation - Weihua Lin; Lifeng Zhang; Xingxiang Ji; Jinquan Wan; Yongwen Ma (Journal of Water Process Engineering, 2025)

Single brand tire wear particles promote toxin-producing of an invasive cyanobacterium - Yuanyuan Mo; Jingxiang Lin; Xi Li; Hans-Peter Grossart; Lifeng Lin; Mekiso Y. Sido; Jun Yang (Environmental Research, 2025)

High-entropy Fe-based spinel oxide for simultaneous electrochemical desalination and dye adsorption in textile wastewater remediation - Ruiqi Yong; Ying Zhao; Chuhan Huang; Pengrui Sun; Wei Zhou; Tianqin Huang; Yuqi Wei; Karunaivel Kajanann; Kailin Fan; Kun Lin; Yiyi Wang; Lifeng Ding; et al. (Chemical Engineering Journal, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Estimating the Mediterranean sea-level trends from 1993 to 2022 showing the consistency of X-TRACK-L2P coastal altimetry with tide gauge data and trend impacts on Egypt's northern coast - Mohamed M. Youssef; Qianqian Li; Ahmed Zaki; Lin Wu; Lifeng Bao (Frontiers in Marine Science, 2025)
In recent decades, sea level has risen markedly along Mediterranean coastlines, highlighting the growing impacts on vulnerable coastal regions. This study analyzed sea-level variability using tide gauge (TG) records from 45 stations, coastal altimetry data (X-TRACK-L2P and X-TRACK/ALES), and virtual altimetry station (VAS) data. Based on TG records from 1993 to 2022, the results reveal positive linear trends, with 11 stations recording rates well above the global mean. The highest rate, 5.281 mm/year, was observed at TARANTO (Station ID: 2095). Strong consistency was also found between TG and X-TRACK-L2P coastal data, with X-TRACK-L2P trends ranging from −3 to 6 mm/year. In addition, sea-level rise in the Adriatic, Aegean, and Levantine sub-basins exceeded the current global mean. The agreement between TG and X-TRACK/ALES data was more limited, observed at only two sites located about 7 km and 20 km apart from the first valid point on the altimetry track, respectively. Furthermore, the findings highlight the diverse impacts of sea-level rise on Egypt's northern coast, where densely populated areas, productive agricultural lands, and cultural heritage sites are particularly at risk. In conclusion, all types of data used indicate positive linear trends in the Mediterranean Sea. In addition, several sites have rates of sea-level trend that exceed the global mean, underscoring the urgent need for proactive adaptation measures.

Improving terrestrial solar-induced chlorophyll fluorescence (SIF) reconstruction through multi-satellite-derived SIF integration: a comparative study in regional scale - Mengting Pan; Xiaofeng Lin; Zhongyong Xiao; Fei Wang; Lifeng Guo; Cuiping Wang; Jinghan Xie; Jingchun Fang (International Journal of Remote Sensing, 2025)

In silico profiling of bisphenol compounds for estrogenic effects via pharmacophore modeling, molecular docking, and dynamics simulations - Lifeng Wang; Ning Li; Linlin Wang; Zengfeng Li; Qiang Li; Jiaqi Tian; Lin Zhang (Journal of Hazardous Materials, 2025)

The conservation of migratory shorebirds needs to account for the different habitat selection patterns across species and between day and night - Shen Zhang; Xiaotong Ren; Ziyin Xiong; Tao He; Kar-Sin Katherine Leung; Wenjie Xue; Li Tian; Lifeng Zhuang; Yi-Chien Lai; Chia-Hsiang Lin; Chi-Yeung Choi (Biological Conservation, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

A five-chamber parallel microbial demineralized fuel cell for removal of microplastics from mine water: Effects, performance, and microbial communities - Lifeng Shi; Xin Li; Yukuo Liu; Xi He; Lin Liu; Xuejing Liu; Fuping Li; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Priming effects by cellulose inputs decrease with warming regardless of the decomposition stages of soil carbon pools - Junjie Lin; Guoxin Lan; Zhenyu Yang; Shuang Zhou; Dafeng Hui; Peng Wang; Shuai Zhang; Lifeng Ping; Shengdao Shan (Plant and Soil, 2025)

Bimetallic active sites with tailored d-bands boost multistep sulfur redox reactions for enhanced lithium-sulfur battery performance - Wei Wang; Jianguo Si; Liguo Yue; Weicai Zhang; Qingqing Chen; Haoliang Huang; Fei Lin; Yang Zhao; Sheng Meng; Lifeng Liu (Chemical Engineering Journal, 2025)

A new Eötvös correction algorithm for marine shipborne gravity survey with irregular nonlinear track - Shi Liu; Lin Wu; Menghan Xi; Guocheng Mao; Lifeng Bao; Yong Wang (Acta Geophysica, 2025)

Preliminary Investigation of the Spatial-Temporal Characteristics and Vertical Dynamics of Internal Solitary Waves in the South China Sea from SWOT Data - Zhikuan Pan; Zhenhe Zhai; Qi Li; Qianqian Li; Lin Wu; Lifeng Bao (Journal of Marine Science and Engineering, 2025)
Internal waves are crucial for understanding oceanographic parameters such as spatiotemporal distribution and energy transfer. They significantly impact ocean circulation, marine ecosystems, and offshore operations. However, studying internal waves is challenging due to their dynamic nature and the need for effective observation methods. This study investigated nonlinear internal solitary waves (ISWs) in the South China Sea using SSHa data from the SWOT satellite mission (Cycles 2 to 20). The distribution patterns and seasonal variations in ISWs were analyzed, revealing that ISWs are more frequently observed in summer while being rarely detected in winter. By combining SSHa observations with a Mode-1 vertical structure model, the isopycnal displacement, velocity fields, and energy characteristics of ISWs were reconstructed. The results show a maximum isopycnal displacement of 160 m at 400 m depth and peak kinetic energy near the surface (~2000 J/m3) and potential energy at a depth of around 300 m (~9000 J/m3). These findings highlight the vertical variability of ISWs and demonstrate the capability of SWOT data in capturing their fine-scale evolution, providing new opportunities for oceanic research and enhancing our understanding of internal waves’ impact on marine environments and ocean circulation.

Interaction between resveratrol and SIRT1: role in neurodegenerative diseases - Lin Zhu; Miaomiao Yang; Lehao Fan; Qiuying Yan; Lifeng Zhang; Ping Mu; Fangjin Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Simultaneous deammoniation and denitrification under vacuum ultraviolet irradiation - Yuanzhong Lin; Shuang Liu; Yuxin Zeng; Wenqing Guo; Tao Guo; Lifeng Yin; Yunrong Dai (Chemosphere, 2024)

Creating smart chlorine-resistant polyamide reverse osmosis membranes via self-healing temperature-responsive nanocontainer functionalization - Qian Yang; Lin Zhang; Yanzhuang Jiang; Song Xu; Beili Pang; Qiong Sun; Na Song; Jianguang Feng; Liyan Yu; Lifeng Dong (Chemical Engineering Journal, 2024)

Multidimensional Evaluation of Altimetry Marine Gravity Models with Shipborne Gravity Data from a New Platform Marine Gravimeter - Bo Wang; Lin Wu; Pengfei Wu; Qianqian Li; Lifeng Bao; Yong Wang (Journal of Marine Science and Engineering, 2024)
With the development of satellite altimetry technology and the application of new altimetry satellites, the accuracy and resolution of altimeter-derived gravity field models have improved over the last decades. Nowadays, they are close enough to shipborne gravimetry. In this paper, multi-source shipborne gravity data in the South China Sea were taken to evaluate the accuracies of two high-precision altimeter-derived marine gravity field models (SS V30.1, DTU17). In these shipborne gravity data, there are dozens of routes’ ship gravimetry data, obtained from the National Geophysical Data Center (NGDC); data were tracked from a marine survey with a commercial marine gravimeter (type KSS31M), and data were tracked from a marine gravimetry campaign that was conducted with a newly developed platform gravimeter (type JMG) in the South China Sea in September 2020. After various data filtering, processing, and calibrations, the shipborne gravity data were validated with crossover points analysis. Then, the processed shipborne data were employed to evaluate the accuracy of the altimeter-derived marine gravity field models. During this procedure, the quality of JMG shipborne gravity data was compared with the results of KSS31M and NGDC data. Analysis and evaluation results show that the crossover points verification accuracies of KSS31M and JMG are 0.70 mGal and 1.61 mGal, which are much better than the accuracy of NGDC, which is larger than 8.0 mGal. In the area where the bathymetry changes slowly, the root mean square error values between altimetry gravity models and KSS31M data are respectively 3.28 mGal and 4.54 mGal, and those of the JMG data are respectively 2.94 mGal and 2.60 mGal. According to the above results, we can conclude that the JMG has the same 1–2 mGal accuracy level as KSS31M and can meet the measurement requirements of marine gravity.

Water scarcity footprint and water saving potential for large-scale green hydrogen generation: Evidence from coal-to-hydrogen substitution in China - Lifeng Du; Yanmei Yang; Xue Bai; Shuo Xu; Ling Lin; Min Liu (Science of The Total Environment, 2024)

Sulfur and phosphorus co-doped FeCoNiCrMn high-entropy alloys as efficient sulfion oxidation reaction catalysts enabling self-powered asymmetric seawater electrolysis - Zhipeng Yu; Danil W. Boukhvalov; Hao Tan; Dehua Xiong; Chuangshi Feng; Jingwei Wang; Wei Wang; Yang Zhao; Kaiyang Xu; Weifeng Su; Xinyi Xiang; Fei Lin; et al. (Chemical Engineering Journal, 2024)

A review of electrooxidation systems treatment of poly-fluoroalkyl substances (PFAS): electrooxidation degradation mechanisms and electrode materials - Lifeng Shi; Chunpeng Leng; Yunlong Zhou; Yue Yuan; Lin Liu; Fuping Li; Hao Wang (Environmental Science and Pollution Research, 2024)

Gelsenicine disrupted the intestinal barrier of Caenorhabditis elegans - Zekai Wu; Jian Zhang; Yajiao Wu; Mengting Chen; Hong Hu; Xinyue Gao; Chutao Li; Maodong Li; Youbo Zhang; Xiaohuang Lin; Qiaomei Yang; Li Chen; et al. (Chemico-Biological Interactions, 2024)

Microbiological mechanisms of sludge property variations under long-term landfill: From micro-omics perspective - Yunxin Xing; Ying An; Lifeng Lin; Peng Peng; Xiaolu Gong; Weijie Hu; Yuqing Ren; Zihang Ma; Jiafu Xi; Jing Cao; Ziyang Lou; Zhen Zhou (Chemical Engineering Journal, 2024)

Visible light-mediated supramolecular framework for tunable CO2 adsorption - Tao Yang; Chunyi Yu; Chen Gu; Yang Liu; Hui Wen; Xiao-Qin Liu; Guoliang Liu; Lifeng Ding; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Antifouling and antibacterial bioactive metabolites of marine fungus (terrein)/polyamide thin-film composite reverse osmosis membranes for desalination applications - Lin Zhang; Qian Yang; Yanzhuang Jiang; Liyan Yu; Na Song; Donglin Zhao; Lina Sui; Lifeng Dong (Desalination, 2024)

Mining subsidence monitoring using distributed scatterers InSAR based on Goldstein filter and Fisher information matrix-weighted optimization - Zeming Tian; Lifeng Zhao; Hongdong Fan; Tao Lin; Tao Li (Natural Hazards, 2024)

High expression of ACKR1 predicts a good prognosis and suppresses sarcoma cell progression via regulating the tumor immune microenvironment - Jinluan Lin; Fude Liang; Lifeng Zheng; Jinyuan Zeng; Jianhua Lin (Journal of Applied Genetics, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

Polarization-dependent photoinduced metal–insulator transitions in manganites - Lina Deng; Weiye Zhang; Hanxuan Lin; Lifen Xiang; Ying Xu; Yadi Wang; Qiang Li; Yinyan Zhu; Xiaodong Zhou; Wenbin Wang; Lifeng Yin; Hangwen Guo; et al. (Science Bulletin, 2024)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

The association of heatwave with drowning mortality in five provinces of China - Zhongguo Huang; Zhixing Li; Jianxiong Hu; Sui Zhu; Weiwei Gong; Chunliang Zhou; Ruilin Meng; Xiaomei Dong; Min Yu; Xiaojun Xu; Lifeng Lin; Jianpeng Xiao; et al. (Science of The Total Environment, 2023)

Nitrogen removal from dewatering liquid of landfill sludge by partial nitrification and denitrification - Zihang Ma; Lifeng Lin; Jiafu Xi; Xiaolu Gong; Jianqiao Wang; Peng Peng; Ying An; Weijie Hu; Jing Cao; Zhichao Wu; Zhen Zhou (Bioresource Technology, 2023)

Enhanced treatment of sludge drying condensate by A/O-MBR process: Microbial activity and community structure - Yin Zhang; Weijie Hu; Lifeng Lin; Shiying Bu; Zhangqin Guan; Jie Zhang; Qiaoying Wang (Chemosphere, 2023)

Homoacetogenesis is altering the metabolic pathway of acidogenic microbiome and combating volatile fatty acid accumulation in anaerobic reactors - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Irini Angelidaki; Nan Lv; Yanlin Li; Guanjing Cai; Lifeng Lin (Journal of Environmental Chemical Engineering, 2023)

Chlorination of microcystin-LR in natural water: Kinetics, transformation products, and genotoxicity - Jinlu Feng; Xi Li; Habasi Patrick Manzi; Claude Kiki; Lifeng Lin; Jiaxing Hong; Wenzhen Zheng; Chuchu Zhang; Shengda Wang; Qiaoting Zeng; Qian Sun (Journal of Environmental Management, 2023)

Improved Bathymetry in the South China Sea from Multisource Gravity Field Elements Using Fully Connected Neural Network - Qianqian Li; Zhenhe Zhai; Qi Li; Lin Wu; Lifeng Bao; Heping Sun (Journal of Marine Science and Engineering, 2023)
Traditional bathymetry inversion methods that rely on an altimetry-derived gravity anomaly (GA) and/or a vertical gravity gradient anomaly (VGG) have been widely used for bathymetry prediction in the South China Sea. However, few studies attempt new methods to combine multisource gravity data to improve the accuracy of the bathymetry. In this study, we introduce a fully connected deep neural network (FC-DNN) to merge GA, VGG, and the deflection of vertical (DOV) to predict the bathymetry in the South China Sea. Single beam sounding depths were used as sample data for neural network training. Independent shipboard depths and GEBCO2023, topo_25.1, and ETOPO2022 models were applied as validation data. The assessment results showed that the FC-DNN model reached a high precision level with an STD of 49.20 m. More than 70% of the differences between the FC-DNN bathymetric model and other depth models were less than 100 m. Furthermore, the spectral analysis results showed that the FC-DNN bathymetry model has stronger energy in medium and short wavelengths than other models, which indicates that additional gravity field element DOVs can recover richer topographic signals in those particular bands.

Efficient separation and comprehensive extraction of aluminum, silicon, and iron from coal fly ash by a cascade extraction method - Xiaodan Zhao; Li Zeng; Jiaming Guo; Qiaoling Zhu; Zhuojun Huang; Lifeng Lin; Xuanang Chen; Jing Cao; Zhen Zhou (Journal of Cleaner Production, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Experimental study on the longitudinal evolution of the overtopping breaching of concrete-face sand-gravel dams - Wen Qiu; Yanlong Li; Lifeng Wen; Lin Wang; Zengguang Xu (Bulletin of Engineering Geology and the Environment, 2023)

Feasibility study on preparing economical and environmentally-friendly high-flowability ultra-high performance cementitious composites with original graded stone powder free recycled manufactured sands - Rui Ma; Lifeng Zhang; Yufeng Song; Gaohang Lin; Xiaoqian Qian; Kuangliang Qian; Shaoqin Ruan (Journal of Cleaner Production, 2023)

An internally damped inertial platform for marine gravimetry and a test case in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

A marine gravimeter based on electromagnetic damping and its tests in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

Gravity disturbance compensation for dual-axis rotary modulation inertial navigation system - Panpan Zhang; Lin Wu; Lifeng Bao; Bo Wang; Hui Liu; Qianqian Li; Yong Wang (Frontiers in Marine Science, 2023)
Gravity disturbance compensation is an important technique for improving the positioning accuracy of high-precision inertial navigation systems (INS). Aiming at the current problems of the resolution of gravity compensation background field and the robustness of gravity compensation algorithm are insufficient for gravity compensation. In this study, the error and frequency characteristics of INS caused by gravity disturbances are investigated. The gravity disturbance with a spatial resolution of 1’ × 1’ from a high-precision satellite altimetry marine gravity field model is preliminarily introduced into the initial alignment and pure INS calculation to implement the gravity compensation of the dual-axis rotary modulation INS. Detailed calculation results show that the east gravity disturbance affects the north attitude, and the north gravity disturbance affects the east attitude in the initial alignment. In the pure INS calculation, the horizontal gravity disturbance causes a navigation error in the form of Schuler oscillation. The INS navigation error caused by horizontal gravity disturbance is mainly affected by its amplitude; however, the horizontal gravity disturbance accuracy from the satellite altimetry model for INS gravity compensation can be ignored in practice. In addition, for low-speed underwater vehicles, the influence of high-frequency gravity disturbance signals on the INS position shows an increasing trend. Finally, the effectiveness of the gravity compensation achieved by the horizontal gravity disturbance from the satellite altimeter model is confirmed by a dynamic shipborne test. The positioning accuracy of the rotary modulation INS is maximally improved by approximately 17.9% after the horizontal gravity disturbance is compensated simultaneously in the pure INS calculation and the initial alignment.

Experimental study on the process of overtopping breach of concrete-faced sand-gravel dam - Yanlong Li; Wen Qiu; Zuyu Chen; Lifeng Wen; Lin Wang (European Journal of Environmental and Civil Engineering, 2022)

Potential and Distribution of Natural Gas Hydrate Resources in the South China Sea - Pibo Su; Lin Lin; Yaoyao Lv; Jinqiang Liang; Yunbao Sun; Wei Zhang; Huice He; Baiquan Yan; Zhanhuai Ji; Lifeng Wang; Feifei Wang; Mengya Cai (Journal of Marine Science and Engineering, 2022)
The amount of natural gas contained in the world’s gas hydrate accumulations is enormous, but these estimates remain highly speculative. So far, it is still challenging to locate spatial distribution of marine gas hydrate and quantitatively characterize the evaluation parameters and systematic improvement of evaluation systems. Considering the systematic review of the key accumulation factors, such as heat flow, deposition rate and total organic carbon in the typical passive continental margin, the evaluation results of global marine gas hydrate resources were analyzed based on the characteristics of gas hydrate geology, geophysics and geochemistry anomalies in the South China Sea. We analyze the problems on the evaluation of marine gas hydrate resources, probing into the geological characteristics and distribution laws of marine gas hydrate resources in the South China Sea, and estimate the parameters for in-place resource evaluation, in which the volume method based on Monte Carlo probability was used to evaluate the gas hydrate potential resources in the South China Sea. The probability distribution ranges from 37.6 billion (with 90% probability) to 117.7 billion (with 10% probability) tons of oil equivalent, with an expected value of 74.4 billion tons of oil equivalent. The study results show that the gas hydrate resource density in the South China Sea is similar to that in the typical sea areas, and the estimated global resources are basically consistent with the assessment results at this stag; this shows that the South China Sea has great potential for gas hydrate resources. The research results can provide guidance for the evaluation of global climate change and the exploration and development of hydrate resources.

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Numerical Simulation of Mine Water Inflow with an Embedded Discrete Fracture Model: Application to the 16112 Working Face in the Binhu Coal Mine, China - Tao Chen; Huiyong Yin; Yutao Zhai; Lin Xu; Cuiyue Zhao; Lifeng Zhang (Mine Water and the Environment, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Mortality burden caused by diurnal temperature range: a nationwide time-series study in 364 Chinese locations - Min Cai; Jianxiong Hu; Chunliang Zhou; Zhulin Hou; Yanjun Xu; Maigeng Zhou; Yize Xiao; Biao Huang; Xiaojun Xu; Lifeng Lin; Tao Liu; Jianpeng Xiao; et al. (Stochastic Environmental Research and Risk Assessment, 2021)

A Two-Step GRIN Lens Coating for In Vivo Brain Imaging - Yupeng Yang; Lifeng Zhang; Zhenni Wang; Bo Liang; Giovanni Barbera; Casey Moffitt; Yun Li; Da-Ting Lin (Neuroscience Bulletin, 2019)

Factors influencing soil enzyme activity in China’s forest ecosystems - Haifeng Zheng; Yang Liu; Jian Zhang; Yamei Chen; Lin Yang; Hongjie Li; Lifeng Wang (Plant Ecology, 2018)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Establishment from the snout and kidney of goldfish, Carassius auratus, of two new cell lines and their susceptibility to infectious pancreatic necrosis virus - Hongli Jing; Longying Gao; Min Zhang; Na Wang; Xiangmei Lin; Lifeng Zhang; Shaoqiang Wu (Fish Physiology and Biochemistry, 2016)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Association of novelty-related behaviors and intravenous cocaine self-administration in Diversity Outbred mice - Price E. Dickson; Juliet Ndukum; Troy Wilcox; James Clark; Brittany Roy; Lifeng Zhang; Yun Li; Da-Ting Lin; Elissa J. Chesler (Psychopharmacology, 2015)

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium - Mingquan Ding; Jiadong Chen; Yurong Jiang; Lifeng Lin; YueFen Cao; Minhua Wang; Yuting Zhang; Junkang Rong; Wuwei Ye (Molecular Genetics and Genomics, 2015)

Discordant patterns of tissue-specific genetic characteristics in the HIV-1 env gene from HIV-associated neurocognitive disorder (HAND) and non-HAND patients - Yabo Ouyang; Lifeng Liu; Yulin Zhang; Lin Yuan; Zhiying Liu; Sufang Yang; Feili Wei; Luxin Qiao; Dexi Chen (Journal of NeuroVirology, 2014)

Detection of grass carp reovirus (GCRV) with monoclonal antibodies - Jing Hongli; Zhang Lifeng; Fang Zhenzhen; Xu Lipu; Zhang Min; Wang Na; Jiang Yulin; Lin Xiangmei (Archives of Virology, 2014)

Evaluation of summer temperature and precipitation predictions from NCEP CFSv2 retrospective forecast over China - Lifeng Luo; Wei Tang; Zhaohui Lin; Eric F. Wood (Climate Dynamics, 2013)

A loop-mediated isothermal amplification method for the detection of members of the genus Ranavirus - Zhang Min; Jing Hongli; Zhang Lifeng; Wang Na; Wu Shaoqiang; Lin Xiangmei (Archives of Virology, 2013)

The distribution and sea–air transfer of volatile mercury in waste post-desulfurization seawater discharged from a coal-fired power plant - Lumin Sun; Shanshan Lin; Lifeng Feng; Shuyuan Huang; Dongxing Yuan (Environmental Science and Pollution Research, 2013)

Cytokines in CSF correlate with HIV-associated neurocognitive disorders in the post-HAART era in China - Lin Yuan; Luxin Qiao; Feili Wei; Jiming Yin; Lifeng Liu; Yunxia Ji; Davey Smith; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)

Discordant genotypic resistance and HIV-1 genetic diversity from paired plasma and cerebrospinal fluid samples in Chinese settings - Lifeng Liu; Yulin Zhang; Feili Wei; Qingxia Zhao; Xicheng Wang; Lin Yuan; Ning Li; Dexi Chen (Journal of NeuroVirology, 2013)